High-performance fixed-bed adsorption using active-site-controlled amine-functionalized adsorbent for naproxen removal: insights into isotherms, kinetics, and regeneration - Yusoff, Nor Aida; Abdullah, Luqman Chuah; Md. Jamil, Siti Nurul Ain; Ting, Teo Ming; Zainuddin, Halimatun Sakdiah (Elsevier, 2025)
The removal of trace pharmaceutical contaminants from wastewater remains a critical challenge owing to the limitations of conventional adsorbents, including slow kinetics, high internal diffusion resistance, and limited reusability. To overcome these challenges, this study presents a novel amine-functionalized adsorbent, EDA- ((PE/PP)-g-GMA), which was synthesized via radiation-induced grafting. The material exhibited exceptional adsorption performance, achieving >96 % naproxen removal in a fixed-bed system under high-flow conditions (7 mL/min) and a short bed height (1 cm). With effluent concentrations below 0.25 mg/L, approaching the regulatory limits established for drinking water, the adsorbent exhibited a high capacity of 300.33 mg/g and successfully treated 3.78 L before reaching breakthrough. The rapid adsorption of naproxen was attributed to the abundance of active functional groups on the surface of EDA-((PE/PP)-g-GMA), following pseudo-second-order kinetics and the Sips isotherm, with active site interactions serving as the rate-limiting step for efficient uptake. Thermodynamic analysis confirmed an exothermic and spontaneous process, whereas FTIR and XPS analyses revealed hydrogen bonding and electrostatic and hydrophobic interactions governing adsorption. Reusability studies demonstrated stable performance over nine cycles without a significant loss of functionality. The fixed- bed adsorption process aligned well with the Thomas, Yoon-Nelson, and BDST models, confirming its scalability. This study demonstrates the effectiveness of the novel adsorbent in fixed-bed systems, highlighting its potential for large-scale environmental remediation while addressing the limitations of current technologies, which is essential for environmental protection and public health preservation against the long-term impacts of pharmaceutical pollution.